The feasibility and effectiveness of telecare consultations in nurse-led post-acute stroke clinics: A study protocol - Arkers Kwan Ching Wong; Jonathan Bayuo; Frances Kam Yuet Wong; Vivian Wai Yan Kwok; Bernard Man Kam Yuen; Ching Sing Fong; Shun Tim Chan; Hoi Lam Pung; Oi Lam Kwek (Digital Health, 2023)
Background Globally, nurse-led post-acute stroke clinics have been developed to provide secondary care services to stroke survivors. Although synthesized evidence supports the idea that the secondary prevention services delivered by nurses in these clinics can improve the functional ability of stroke survivors and reduce their readmission rates, long travel and waiting times, high costs, and the pandemic have limited the utilization of such clinics. Telecare consultations are a new modality for expanding public access to healthcare services, although how it can be applied in nurse-led clinics has not been reported. Objective The aim of this study is to determine the feasibility and effects of telecare consultations in nurse-led post-acute stroke clinics. Methods The study adopts a quasi-experimental design. The participants will receive three secondary stroke care consultations in 3 months provided via telecare by experienced advanced practice nurses. The outcome measures include feasibility (reasons for refusing to participate and for dropping-out, the attitudes and satisfaction of both the advanced practice nurses and their patients towards the programme), and preliminary effectiveness (degree of disability after stroke, activities of daily living, instrumental activities of daily living, health-related quality of life, depression) outcomes. Data will be collected at pre-(T1) and post-(T2) intervention. Conclusions The findings of this study may help facilitate the implementation of telecare consultations in a nurse-led post-acute stroke clinic, which may benefit the stroke survivors who are having mobility restrictions from accessing customary healthcare services and may protect them from being exposed to the infectious risk.